Modern advances in spinal cord regeneration: hydrogel combined with neural stem cells - Rybachuk, Oksana; Nesterenko, Yuliia; Zhovannyk, Valeriia (Frontiers in Pharmacology, 2024)
Severe spinal cord injuries (SCI) lead to loss of functional activity of the body below the injury site, affect a person's ability to self-care and have a direct impact on performance. Due to the structural features and functional role of the spinal cord in the body, the consequences of SCI cannot be completely overcome at the expense of endogenous regenerative potential and, developing over time, lead to severe complications years after injury. Thus, the primary task of this type of injury treatment is to create artificial conditions for the regenerative growth of damaged nerve fibers through the area of the SCI. Solving this problem is possible using tissue neuroengineering involving the technology of replacing the natural tissue environment with synthetic matrices (for example, hydrogels) in combination with stem cells, in particular, neural/progenitor stem cells (NSPCs). This approach, primarily, can provide maximum stimulation and support for the regenerative growth of axons of damaged neurons and their myelination. In this review, we consider the currently available options for improving the condition after SCI (use of NSC transplantation or/and replacement of the damaged area of the SCI with a matrix, specifically a hydrogel); and we. We emphasize emphasise the expediency and effectiveness of the hydrogel matrix+NSCs complex system used for the reconstruction of spinal cord tissue after injury. Since such a complex approach (a combination of tissue engineering and cell therapy), in our opinion, allows not only to creation of conditions for supporting endogenous regeneration or mechanical reconstruction of the spinal cord, but also to strengthen endogenous regeneration, prevent the spread of the inflammatory process, and promote the restoration of lost reflex, motor and sensory functions of the injured area of spinal cord.